Lung SBRT credentialing in the Canadian OCOG-LUSTRE randomized trial. (November 2022) - Swaminath, Anand; Wierzbicki, Marcin; Parpia, Sameer; Kundapur, Vijayananda; Faria, Sergio; Ahmed, Naseer; Bujold, Alexis; Hirmiz, Khalid; Owen, Timothy; Leong, Nelson; Ramchandar, Kevin; Filion, Edith; et al.
Highlights: We report on the credentialing experience of a Phase III trial of SBRT versus hypofractionated RT for stage I lung cancer. Elements included a site survey, phantom test, and a standardized case for a peripheral and central tumour. Approximately 1/3 of plans required resubmission due to major deviations, but were not biased towards centre experience versus not. There was contour variability demonstrated, whereas target coverage and dose constraints were largely per-protocol. Such an exercise is important for studies that rely on high precision radiotherapy, and to ensure optimal trial quality. Abstract: Purpose: To report on the Stereotactic Body Radiation Therapy (SBRT) credentialing experience during the Phase III Ontario Clinical Oncology Group (OCOG) LUSTRE trial for stage I non-small cell lung cancer. Methods: Three credentialing requirements were required in this process: (a) An institutional technical survey; (b) IROC (Imaging and Radiation Oncology Core) thoracic phantom end-to-end test; and (c) Contouring and completion of standardized test cases using SBRT for one central and one peripheral lung cancer, compared against the host institution as the standard. The main hypotheses were that unacceptable variation would exist particularly in OAR definition across all centres, and that institutions with limited experience in SBRT would be more likely to violate per-protocol guidelines. Results: Fifteen Canadian centres participated of which 8 were new, and 7 were previously established (≥2 years SBRT experience), and all successfully completed surveys and IROC phantom testing. Of 30 SBRT test plans, 10 required replanning due to major deviations, with no differences in violations between new and established centres (p = 0.61). Mean contouring errors were highest for brachial plexus in the central (C) case (12.55 ± 6.62 mm), and vessels in the peripheral (P) case (13.01 ± 12.55 mm), with the proximal bronchial tree (PBT) (2.82 ± 0.78 C, 3.27 ± 1.06 P) as another variable structure. Mean dice coefficients were lowest for plexus (0.37 ± 0.2 C, 0.37 ± 0.14 P), PBT (0.77 ± 0.06 C, 0.75 ± 0.09 P), vessels (0.69 ± 0.29 C, 0.64 ± 0.31 P), and esophagus (0.74 ± 0.04 C, 0.76 ± 0.04 P). All plans passed per-protocol planning target volume (PTV) coverage and maximum/volumetric organs-at-risk constraints, although variations existed in dose gradients within and outside the target. Conclusions: Clear differences exist in both contouring and planning with lung SBRT, regardless of centre experience. Such an exercise is important for studies that rely on high precision radiotherapy, and to ensure that implications on trial quality and outcomes are as optimal as possible.